The midwife's role in achieving the Sustainable Development Goals: protect and invest together - the Swedish example - Helena Lindgren; Malin Bogren; Ingrid Osika Friberg; Marie Berg; Gabriella Hök; Kerstin Erlandsson (Taylor & Francis Group, 2022)
'The midwife's role in achieving the Sustainable Development Goals: Protect and Invest Together' is a report providing the reader the opportunity for understanding and appreciating the history of midwifery in Sweden and the interlinked nature of the United Nation's SDGs supporting health and wellbeing of women and children. To realise the opportunity to have a country with well-educated midwives of high academic standard, and, at the same time, promoting gender equality and equity we need to protect and invest together in midwives. This paper provides the foundation for a revitalised discussion on midwives' role for women and child health in the 21st century. The full Swedish Midwifery report was published in October 2021.